Edukasi Ibu-Ibu Pkk Desa Jimus Polanharjo Klaten Tentang Pencegahan Stunting Pada Balita - Sri Rahayu; Nasrawati (WASATHON Jurnal Pengabdian Masyarakat, 2023)
Stunting is a chronic malnutrition problem caused by a lack of nutrition for a long time, resulting in growth disorders in children, namely the child's height is lower or shorter (dwarf) than the standard age and is a problem that can actually be prevented. The problem that occurs with PKK mothers in Jimus village is the desire to understand how to prevent stunting under-fives so that there are no stunting under-fives in Jimus village. So we, as executors of community service in Jimus village, are educating PKK mothers in Jimus village about stunting prevention according to Presidential Decree number: 72 of 2021, namely Accelerating the Reduction of Stunting in Toddlers. In the implementation using the educational lecture method about stunting prevention which began with a pretest and ended with a post test on PKK mothers from the village of Jimus Polanharjo, which was carried out on March 15 2022 with the result that there were 48 PKK mothers who attended community service events. with the pretest results, it was found that 58% did not know what the risk factors for stunting toddlers were with their prevention and posttest 94% had understood and understood how to prevent stunting toddlers. It is recommended to the public, especially mothers, to prevent stunting by fulfilling nutritional intake during pregnancy, childbirth and children before the age o f 2 years.